Glycemic load effect on fasting and post-prandial serum glucose, insulin, IGF-1 and IGFBP-3 in a randomized, controlled feeding study - Runchey, Shauna S. (2012)
BACKGROUND/OBJECTIVES: The effect of a low glycemic load (GL) diet on insulin-like growth factor-1 (IGF-1) concentration is still unknown but may contribute to lower chronic disease risk. We aimed to assess the impact of GL on concentrations of IGF-1 and IGFBP-3. SUBJECTS/METHODS: We conducted a randomized, controlled crossover feeding trial in 84 overweight-obese and normal weight healthy individuals using two 28-day weight-maintaining high- and low-GL diets. Measures were fasting and post-prandial concentrations of insulin, glucose, IGF-1 and IGFBP-3. 20 participants completed post-prandial testing by consuming a test breakfast at the end of each feeding period. We used paired t-tests for diet-component and linear mixed models for biomarker analyses. RESULTS: The 28-day low-GL diet led to 4% lower fasting concentrations of IGF-1 (10.6 ng/mL, p=0.04) and a 4% lower ratio of IGF-1/IGFBP-3 (0.24, p=0.01) compared to the high-GL diet. The low-GL test breakfast led to 43% and 27% lower mean post-prandial glucose and insulin responses, respectively; mean incremental areas under the curve for glucose and insulin, respectively, were 64.3±21.8 (mmol/L/240min) (p<0.01) and 2253±539 (μU/mL/240min) (p<0.01) lower following the low- compared to the high-GL test meal. There was no effect of GL on mean HOMA-IR or on mean integrated post-prandial concentrations of glucose-adjusted insulin, IGF-1 or IGFBP-3. We did not observe modification of the dietary effect by adiposity. CONCLUSIONS: Low-GL diets resulted in 43% and 27% lower post-prandial responses of glucose and insulin, respectively, and modestly lower fasting IGF-1 concentrations. Further intervention studies are needed to weigh the impact of dietary GL on risk for chronic disease.